Comparative Efficacy of Histrelin Acetate and hCG for Inducing Ovulation in Brazilian Northeastern Jennies (Equus africanus asinus) - Oliveira, Sidnei N. [UNESP]; Segabinazzi, Lorenzo G.T.M. [UNESP]; Canuto, Lucas [UNESP]; Lisboa, Fernando P.; Medrado, Felipe E. [UNESP]; Dell'Aqua, Jose A. [UNESP]; Aguiar, Antonio J.A. [UNESP]; Papa, Frederico O. [UNESP] (My University, 2020)
The goal of this study was to compare the efficiency of histrelin acetate (GnRH analog) and human chorionic gonadotropin (hCG) to hasten ovulation in Brazilian Northeastern jennies (Equus africanus asinus). Thirty cycles of ten jennies were randomly assigned in one of the three groups: G0 (control group), saline; G1, 250 μg of histrelin acetate; G2, 2500 IU of hCG. Jennies were evaluated by transrectal palpation and ultrasonography, and had the administration of an ovulation-inducing agent when a follicle measuring between 29 and 32 mm of diameter was diagnosed. Jennies were monitored every 6 hours by transrectal ultrasonography until ovulation. The interval between prostaglandin administration and ovulation was lower (P < .05) in jennies from the G1 (145.2 ± 34.6 hours) and G2 (147.4 ± 27.3 hours) groups compared with the control cycle (220.0 ± 41.8 hours). Both treatments (G1, 41.15 ± 3.5 hours; G2, 37.8 ± 2.5 hours) also reduced (P < .05) the interval that jennies took to ovulate after the administration of the ovulation-inducing agent compared with the control (81.8 ± 28.8 hours). All jennies from G1 and G2 ovulated up to 48 hours after ovulation induction, whereas 100% of jennies in the control cycle ovulated later (>48 hours from the administration of saline). In conclusion, both histrelin acetate and hCG at the used dose are efficient ovulation-inducing agents in jennies promoting ovulation up to 48 hours after administration.
Keywords: Donkeys; Estrous cycle; GnRH analog; Reproduction